LEGAL PROTECTION AGAINST CHILDREN ONLINE PORNOGRAPHIC CRIME OBJECTS BASED ON LAW OF THE REPUBLIC OF INDONESIA NUMBER 44 OF 2008 CONCERNING PORNOGRAPHY - Amsori, Amsori; Rizky Isnia, Debby (IBLAM LAW REVIEW, 2021)
The issue of legal protection for children who are the object of crime in Indonesia is very important because they are the future generation of the nation. One of the threats to children is the influence of online pornography, where the online world is now common to society. So that the public knows whether the state has made efforts to provide legal protection for children who are objects of online pornography crimes through the Pornography Law and to find out the extent to which the Pornography Law is used as a reference to get legal protection from perpetrators of online pornography crimes. In this research, it is analyzed juridically with deductive explanation regarding the provisions contained in the Law on Pornography in relation to the legal protection of children as objects of pornography crimes. It was found that since the early part of the Pornography Law has shown the spirit of legal protection for children starting from the definition of age limits categorized as children, the purpose of the law which clearly contains the words to protect children, to criminal provisions that stipulate an additional sentence of one third of the maximum a criminal threat if the pornographic crime involves a child. In decision Number 1363 / Pid.Sus / 2017 / PN JKT.SEL, the Pornography Law is mentioned as a reference in the ruling other than the Law on Electronic Information and Transactions, however in imprisonment and fines in the verdict it does not indicate that what was used is a criminal provision in the Pornography Law. In fact, according to the Criminal Code, if there are different rules, the heavier the criminal provisions are used. From the foregoing, it can be seen that the Pornography Law is here to answer the need for legal protection for children as objects of online pornography crimes. Then, criminal decisions related to pornography crimes should consistently refer to the Pornography Law in order to play an optimal role in preventing similar crimes from recurring and ensuring legal protection for children.